Correlation Between Creatinine And Electrolyte In CKD Patient - Samsuria, Indranila Kustarini (2020, 2020)
Introduction: Chronic kidney disease (CKD) reduce progressively glomerular filtration rate (GFR), which usually results in an dearrangement of electrolyte. Aim of this study:  is to evaluate the correlation between Creatinine and the electrolyte  in CKD. Methods : This cross sectional study include CKD patients who treated in Jepara Hospital from April 2019 to June 2019. Statistical analysis to correlate between creatinine and electrolyte in each group was performed using Spearman correlation test. Results :  We studied 30 subjects, 11 male (36.7%) and 19 female (63,3%) with      the average of age 62 years   (mean age 61.37± 6.81years old). Correlation between creatinine with Na (r= -0.341;p=0.065)  , K (r=0.416; p=0.022), Cl (r=0.385; p=0.036), Ca(r=0.313 ;p=0.092), Mg(r= -0.324; p=0.080). Conclusion : There is a significant moderate  positive correlation between creatinine and  Potassium (K) and weak positive  correlation between creatinine and chloride (Cl).